2022
DOI: 10.3390/v14030599
|View full text |Cite
|
Sign up to set email alerts
|

Seed Transmission of Three Viruses in Two Pear Rootstock Species Pyrus betulifolia and P. calleryana

Abstract: Viral seed transmission causes the spread of many plant viral diseases. Pyrusbetulifolia and P. calleryana are important rootstock germplasms for pear production in China. This study revealed the widespread infection of apple stem grooving virus (ASGV), apple chlorotic leaf spot virus (ACLSV), and apple stem pitting virus (ASPV) in maternal trees of P. betulifolia and P. calleryana by nested multiplex reverse transcription-polymerase chain reaction (nmRT-PCR) assays. Seeds from eight P. betulifolia and two P. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 64 publications
2
4
1
Order By: Relevance
“…Similarly to the work of Li et al [ 21 ] on the transmission of ACLSV, ASGV, and ASPV in two pear rootstock species, we found that these three viruses can be detected from the seedcoats of seeds extracted from fruits of infected maternal trees. The rates at which these three viruses were detected in untreated seeds were higher in our experiments (92.7%, 95.9%, and 92.1%, respectively) vs. the rates reported by Li et al [ 21 ] (40.4%, 73.9%, and 21.2%, respectively).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Similarly to the work of Li et al [ 21 ] on the transmission of ACLSV, ASGV, and ASPV in two pear rootstock species, we found that these three viruses can be detected from the seedcoats of seeds extracted from fruits of infected maternal trees. The rates at which these three viruses were detected in untreated seeds were higher in our experiments (92.7%, 95.9%, and 92.1%, respectively) vs. the rates reported by Li et al [ 21 ] (40.4%, 73.9%, and 21.2%, respectively).…”
Section: Discussionsupporting
confidence: 89%
“…Similarly to the work of Li et al [ 21 ] on the transmission of ACLSV, ASGV, and ASPV in two pear rootstock species, we found that these three viruses can be detected from the seedcoats of seeds extracted from fruits of infected maternal trees. The rates at which these three viruses were detected in untreated seeds were higher in our experiments (92.7%, 95.9%, and 92.1%, respectively) vs. the rates reported by Li et al [ 21 ] (40.4%, 73.9%, and 21.2%, respectively). These differences may reflect biological differences between the host species studied ( P. betulifolia and P. calleryana vs. M. domestica ), genetic divergence among virus isolates, or differences in the virus detection methodologies employed.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The natural spread of ACLSV in the field has been reported, but suggested transmission by eudosylaimoid nematodes, aphids (Myzus persicae) or pollen was not confirmed (Mink, 1993;Šutić et al, 1999). Recently, Li et al (2022) demonstrated the presence of ACLSV in seeds from infected P. betulifolia and P. calleryana trees, indicating that the virus can also be transmitted by seeds. Previously, ACLSV has been detected in apple and quince seedlings (Posnette & Cropley, 1964).…”
Section: Hostsmentioning
confidence: 99%
“…Infections by pathogens are positively connected with economic loss and raise concerns regarding food security. For instance, viral infection in pear plants successfully triggers physiological and biochemical activities [109,110]. Similarly, bacterial attack can also reduce plant productivity, as indicated by lower biochemical and metabolic activities.…”
Section: Pathogen Infectionmentioning
confidence: 99%